Sarsasapogenin protects hair cells from cisplatin-induced ototoxicity by attenuating apoptosis and ferroptosis via alleviating oxidative stress - Chen, Zhifeng; Xie, Ting; Chen, Chenyu; Lin, Tingting; Wu, Xiaobo; Chen, Yuqing; Lin, Yanchun; Luo, Xiaoyang; Zeng, Chaojun; Lin, Chang (Frontiers in Pharmacology, 2025)
Background and PurposeCisplatin is a widely used chemotherapy drug for the treatment of solid tumours, but its clinical benefit is often limited by ototoxicity, leading to irreversible sensorineural hearing loss. However, there is a lack of effective strategies to prevent hearing loss caused by cisplatin in adults, while sodium thiosulfate is approved by the Food and Drug Administration in the United States for only use at the pediatric level. Sarsasapogenin, a natural compound of the Anemarrhena asphodelides, has antioxidant and neuroprotective properties, which suggest that it may attenuate the ototoxicity induced by cisplatin. The aim of this study is to evaluate the otoprotective effects of sarsasapogenin and its underlying mechanism as a potential therapeutic intervention for the prevention of ototoxicity induced by cisplatin.MethodsCell viability was assessed by CCK-8 and cell apoptosis was assessed by flow cytometry. Reactive oxygen species (ROS) levels and mitochondrial dysfunction were quantified by immunofluorescence. In addition, expression of the molecules involved in apoptosis and ferroptosis was analyzed by qRT-PCR and Western blot. In vivo auditory function was evaluated by auditory brainstem response testing, and the survival of hair cells in the cochlea was quantified by immunolabeling with myosin-VIIa.ResultsSarsasapogenin significantly alleviated cisplatin-induced oxidative stress and restored mitochondrial function in House Ear Institute-Organ of Corti 1 (HEI-OC1) cells. Furthermore, sarsasapogenin effectively protected against cisplatin-induced sensorineural hearing loss and hair cell degeneration in vivo. Mechanistically, the protective effects of sarsasapogenin were primarily mediated through the inhibition of apoptosis and ferroptosis, both in vitro and in vivo.ConclusionThis study provides compelling evidence for the otoprotective effects of sarsasapogenin, suggesting its potential as a therapeutic intervention to prevent cisplatin-induced hearing loss.